2018
DOI: 10.1002/jcp.26551
|View full text |Cite
|
Sign up to set email alerts
|

High amplitude and low frequency cyclic mechanical strain promotes degeneration of human nucleus pulposus cells via the NF‐κB p65 pathway

Abstract: Disc degeneration alters the structure and function of intervertebral discs and is the basis of spinal degenerative diseases. To establish the molecular mechanism of intervertebral disc degeneration caused by mechanical strain, this study examined the effects of different amplitude (3%, 9%, 19%) cyclic mechanical strain (CMS) at a low frequency (0.01 Hz) on the secretion of cartilage extracellular matrix, expression of inflammatory cytokines and catabolic proteases, and activation of NF-κB signaling pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Our model exhibits features of stretch-induced low-grade mechanoflammation, representative of early-stage AF injury [ 12 ]. In agreement with previous studies [ 13 , 14 , 15 , 16 , 17 ], the hyperphysiological cyclic stretching of AF cells induced an increase in gene expression of IL6, IL8, COX2 and MMP1. This pro-inflammatory response was transient and decreased with increasing stretching durations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our model exhibits features of stretch-induced low-grade mechanoflammation, representative of early-stage AF injury [ 12 ]. In agreement with previous studies [ 13 , 14 , 15 , 16 , 17 ], the hyperphysiological cyclic stretching of AF cells induced an increase in gene expression of IL6, IL8, COX2 and MMP1. This pro-inflammatory response was transient and decreased with increasing stretching durations.…”
Section: Discussionsupporting
confidence: 92%
“…This is compatible with a single continuous loading event, rather than a repetitive loading regime. The reduction of COL2A1 and ACAN mRNA in response to cyclic stretching, also previously reported by another study [ 13 ], confirms the degenerative purpose of our hyperphysiological stretching regime. The moderate but significant increase in PGE2 release caused by hyperphysiological cyclic stretching further confirms the COX2 gene expression increase.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, these mechanical demands are reported to be initiating factors for disc degeneration in some cases [16]. Recently, increasing evidence has indicated that cell-mediated matrix remodeling is the secondary response to mechanical stimulation during daily activities, which ultimately leads to degenerative changes [8,12,13,24–26]. For intervertebral disc, much progress has been made in explaining mechanobiologic effects of NP tissue, whereas much less has been done in investigating biological responses of AF tissue to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the elasticity and loadresistance of intervertebral disc lessen. Recent studies found that a series of inflammatory factors involved in the IDD process, which closely related to the occurrence and development of IDD [1][2][3]. However, the role of various inflammatory factors and the molecular mechanisms involved in IDD is not fully definitude.…”
Section: Introductionmentioning
confidence: 99%